Structural mapping and tuning of mixed halide ions in amorphous sulfides for fast Li-ion conduction and high deformability. Issue 14 (20th March 2023) - Kim, Ji-Su; Kim, Young Jung; Han, Daseul; Nam, Kyung-Wan; Kwon, Gihan; Heo, Tae Wook; Jung, Hun-Gi; Yoon, Kyung Joong; Kim, Hyoungchul
Abstract : A glassy sulfide with fast Li-ion conduction and high deformability was developed and analyzed by combinatorial atomic-level approaches. Abstract : Amorphous sulfides are among the most promising candidates for solid electrolytes (SEs) owing to their excellent deformability and acceptable Li-ion conductivity ( σ ion ) at room temperature. However, the complex atomic structure of these amorphous materials without long-range ordering results in a lack of structural understanding and difficulties in tuning material properties. In this study, we performed structural mapping of glassy sulfide SEs composed of various anion clusters using a combinatorial atomic level analysis of synchrotron X-ray-based pair distribution function (PDF) and reverse Monte-Carlo (RMC) methods, demonstrating the potential to tune σ ion in glass SEs. First, we prepared a new glassy sulfide with a mixed anion framework of two halogens (Br and I) as atomic anions, with PS4 3− molecular anions in a Li2 S–P2 S5 -based glass SE. At a specific Br content, [(Li2 S)0.658 (LiI0.9 LiBr0.1 )0.342 ]0.825 [P2 S5 ]0.175 recorded a σ ion of 2.27 mS cm −1, the highest value for any glass sulfides reported to date; however, its elastic modulus was still suppressed to 14.48 GPa. PDF and RMC calculations successfully provided structural mapping of anion clusters, including two halogens. Molecular dynamics simulations of each composition confirmed that flexible coordination caused by the rattling of small polarizable Br ions in the mixed halogens of glassy SEs contributed to the superior σ ion . Our results may provide new insights into the design of superior glassy SEs that play key roles in all-solid-state batteries requiring fast Li-ion conduction and high deformability.